THE SEQUENCE SPACE Enq (M, p, s) AND Nk- LACUNARY STATISTICAL CONVERGENCE - Braha, Naim L.; Et, Mikail (Duke Univ Press, 2013)
In this paper we define the sequence space E-n(q) (M, p, s) by using an Orlicz function and we study various properties and obtain some inclusion relations involving this space. We give some relations between N-k - lacunary statistical convergence and strongly N-k- lacunary convergence.
Keywords: Orlicz function; sequence space; Euler mean; statistical convergence